Profil Isoflavon Sebagai Fitoestrogen pada Berbagai Leguminoceae Lokal - Cicilia Novi Primiani; Joko Widianto; Winda Rahmawati; Gabriella Chandrakirana (Universitas Sebelas Maret, 2018)
Isoflavones are chemical compounds with estrogen-like structures, and are found in many Leguminoceae plants. The isoflavone compounds present in plants are often called phytoestrogen compounds.This study aims to analyze isoflavone compounds in local Leguminoceae seeds, is Cajanuscajan L. Vignaradiata, Arachishypogaea, Phaseolusvulgaris L. and VignaunguiculataL .Analytical method using High Performance Liquid Chromatography (HPLC) with control system: SCL 10 AVP, solvent delivering unit: LC 20 AT, Column oven: CTO 10 ASVP, detector: SPD 20 A UV Vis Detector, Column: C 18,5 µm Shimadzu 120 x 4.6 mm, Column temperature 25o C, Mobile phase: A. Phosphoric acid in water 0,1% B. Acetonitrile 25%, Mobile phase method: Isocratic method, Flow rate: 1 ml/min, Injection volume: 5 µl, Wavelenght detector: UV 280 nm, Run time 40 min. The results showed the presence of daidzin, glycitin, genistin, daidzein, glycitein, dan genistein compounds.probing prompting feasible used to improve student learning outcomes MTs Al-Musthofawiyah Palang.